Analysis of RFID technology usage for luggage management in the airline industry. (1st January 2012) - Guah, Matthew Waritay; Joseph, Rhoda C.
Airlines are a vital part of the transportation industry, responsible for the movement of people and products. Air passenger luggage is a key component of such services. A primary function of radio frequency identification (RFID) in the airline industry is to improve customer service and reduce associated costs by effectively tracking passenger luggage. In the commercial airline industry, fierce competition and declining margins make adoption of technologies such as RFID an attractive option. In this paper, we analyse two airlines to identify the antecedents and outcome of the RFID adoption in the airline industry with specific reference to the management of customer luggage. Ultimately, we identify that RFID is a necessary but insufficient technology for airlines seeking to gain a competitive advantage in the ever-dynamic airline industry.